Absolute characterization of high numerical aperture microscope objectives utilizing a dipole scatterer - Jörg S. Eismann (Nature Publishing Group, 2021)
An absolute characterization technique for microscope objectives is presented, working without a calibrated reference element. To achieve this, a reference wave is created by a sub-wavelength object.